Breast cancer: development of early non-invasive diagnostics to reduce disease mortality and psychological outcomes - Jeznach, Magdalena; Jordan, Philip; Akoulitchev, Alexandre (Psychoonkologia, 2013)
Worldwide, breast cancer is the most common invasive cancer in women and accounts for the highest number of deaths in women. Population-based mammography screening has been introduced throughout the developed world for early diagnosis of women at risk and to reduce mortality. Mammography is currently the gold standard for detection of all forms of breast cancer. Despite the fact that mammography screening has been proven to reduce mortality rate, the test has its limitations. Many studies have shown that mammography leads to false results, over-diagnosis and over-treatment. In fact, many cases of low-risk cancers such as carcinomas in situ , which do not require treatment are detected by mammography. Receiving a false or delayed diagnosis may result in considerable psychological problems and lack of trust towards current diagnostic methods. Thus, there is a great need for better diagnostic technologies to be developed using more sensitive and non-invasive techniques to boost cancer diagnostic accuracy when used in combination with the existing methods. Increased knowledge of molecular heterogeneity in breast cancer and advances in molecular research have opened new opportunities for early breast cancer detection. As a result, stratification of tumours based on their molecular signatures and tailored personalised treatments have been made possible. Several cutting edge tests have been developed for diagnosis or prognosis of breast cancer with the use of this technology. Novel non-invasive diagnostics based on epigenetic differences in key breast cancer biomarkers offers the same day diagnosis with high specificity and sensitivity regardless of the type and stage of breast cancer.